Determinants of Accounting Student Readiness to Face the World of Work - I Gusti Ngurah Agung Dananjaya; Ni Ketut Rasmini; I Putu Sudana; Putu Agus Ardiana (Universitas Pendidikan Ganesha, 2023)
In the Indonesian context, the disparity in the quality of university graduates vis-à-vis workforce expectations remains a significant phenomenon. This research sets out to investigate the crucial determinants affecting the readiness of accounting students to navigate the professional realm, focusing on knowledge in the world of work, soft skills, and locus of control. Employing a survey methodology with a questionnaire, data were meticulously analyzed using multiple linear regression through the SPSS program. The findings underscore a positive correlation between knowledge in the world of work, soft skills, locus of control, and the work readiness of accounting students at the Faculty of Economics and Business, Udayana University. Although the overall work readiness scores are commendable, the study advocates for continuous maintenance and improvement initiatives to optimize students' preparedness for the workforce. The implication is that Udayana University, and potentially other educational institutions, could play a pivotal role by actively facilitating activities geared towards enhancing students' workplace skills. By doing so, these institutions contribute not only to academic excellence but also to the practical readiness of graduates for the professional challenges they will encounter in the world of work.